2015
DOI: 10.1039/c5ob00023h
|View full text |Cite
|
Sign up to set email alerts
|

A benzotriazole-mediated route to protected marine-derived hetero-2,5-diketopiperazines containing proline

Abstract: A procedure for the cyclization of dipeptidoyl benzotriazolides containing proline derivatives promoted by triethylamine under MW activation is introduced. The reaction is general for a variety of dipeptidoyl benzotriazolides and represents a very practical and convenient method for the preparation of Pro- or Hyp-derived 2,5-diketopiperazines (2,5-DKPs) and bis-DKPs with a disulfide linker. This method can be used for the construction of 2,5-DKP compound libraries and for the synthesis of natural products with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Functionalization of the α-Csp 3 –H bond of nitrogen-containing cyclic amino acids has attracted great attention, because of their significance as versatile building blocks in the synthesis of N -heterocyclic natural products and biomolecules. ,, In 2009, Liang et al reported the functionalization of α-amino acids by one-pot three-component tandem decarboxylative coupling strategy, using CuI as a homogeneous catalyst …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalization of the α-Csp 3 –H bond of nitrogen-containing cyclic amino acids has attracted great attention, because of their significance as versatile building blocks in the synthesis of N -heterocyclic natural products and biomolecules. ,, In 2009, Liang et al reported the functionalization of α-amino acids by one-pot three-component tandem decarboxylative coupling strategy, using CuI as a homogeneous catalyst …”
Section: Resultsmentioning
confidence: 99%
“…Functionalization of the α-Csp 3 −H bond of nitrogencontaining cyclic amino acids has attracted great attention, because of their significance as versatile building blocks in the synthesis of N-heterocyclic natural products and biomolecules. 35,49,50 In 2009, Liang et al reported the functionalization of α-amino acids by one-pot three-component tandem decarboxylative coupling strategy, using CuI as a homogeneous catalyst. 51 In order to check the versatility of the Cu@SiO 2 -NS nanocatalyst, we further extended the scope of the present method for decarboxylative tandem coupling among proline (6), 3-nitrobenzaldehyde (1c), and phenylacetylene (3) or phenylpropiolic acid (3a) to afford aliphatic N-heterocycle such as 1-benzyl-2-(phenylethynyl)pyrrolidine in excellent yield, as shown in Scheme 3.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%